Connected Struggles: Catholics, Nationalists, and Transnational Relations between Mexico and Quebec, 1917-1945 - MAURICE DEMERS (McGill-Queen's University Press, 2014)
Located roughly one hundred kilometres south of Quebec City, in the undulating landscape of the Appalachians, La Guadeloupe stands out as a village with an unusual name. Exoticism is not often associated with rural Quebec’s place names. Most municipalities took their French names from the Catholic parishes with which they share borders and Beauce’s toponymy is no exception, apart from a few English names present on the region’s map (mainly referring to the cantons or towns along the old railway line). The name Notre- Dame-de-la-Guadeloupe may come from its parish, but no other town in Quebec honours the Virgin Mary’s 1531 appearance to Juan Diego, an Indio from Mexico. On the face of it, this fact seems inconsequential. And in many ways, it is. But the events that brought about this namesake – the emergence of transnational connections between French Canadian nationalists and devout Catholics in Mexico in the first half of the twentieth century – nonetheless discloses revealing aspects of power relations in Canada and Mexico. Who knew nationalists from Quebec and Catholic militants from Mexico once shared a common cause, a cause that influenced the international relations of their respective countries? The field of transnational studies is flourishing and has produced significant breakthroughs, revaluating the history of Latin American nations in light of their global interactions. Nevertheless, scholars have largely shied away from exploring Canadian-Latin American relations in the twentieth century through that lens. Many scholars would argue that the foreign ministries in Ottawa and Latin America have always conceived the connections between their countries, first and foremost, in economic and political terms. Yet, this perspective does not tell the whole story about North-South interactions involving Canadians and Latin Americans. This book questions the premises of this longheld view in academia. Indeed, the following five chapters offer a unique perspective on the subject by highlighting how civilian actors from the French-speaking province had developed an important web of sociocultural connections in Latin America in the first part of the twentieth century; it also shows that Mexican Catholics established good connections with co-religionists from Canada at the same time. Using the case of Mexican-French Canadian transnational relations to demonstrate these points, my book puts forward the argument that Catholics in both nations saw their struggles over cultural identity as interconnected and used their expressions of solidarity as political capital. This camaraderie, when analyzed, helps us understand the process by which identity politics influenced the history of Canada and Mexico’s diplomacy in the Americas and created lasting networks of solidarity. The North-South connections largely initiated by the Québécois took shape before the creation of the Canadian International Development Agency (cida) or the intensification of Catholic missionary efforts in the region in the 1960s. Catholic nationalists in French Canada and Mexico laid the bases for particular ties between Quebec and Latin America by making mutually supportive gestures in favour of their cultural struggles at a time when the World Wars in Canada and the Revolution in Mexico marginalized voices of dissent. La Guadeloupe is a reminder of that North- South solidarity.